Telomere shortening is associated with corticosterone stress response in adult barn swallows. Issue 1 (9th March 2021) - Costanzo, Alessandra; Ambrosini, Roberto; Parolini, Marco; Caprioli, Manuela; Secomandi, Simona; Rubolini, Diego; Fusani, Leonida; Canoine, Virginie
Abstract: When vertebrates face stressful events, the hypothalamic–pituitary–adrenal (HPA) axis is activated, generating a rapid increase in circulating glucocorticoid (GC) stress hormones followed by a return to baseline levels. However, repeated activation of HPA axis may lead to increase in oxidative stress. One target of oxidative stress is telomeres, nucleoprotein complexes at the end of chromosomes that shorten at each cell division. The susceptibility of telomeres to oxidizing molecules has led to the hypothesis that increased GC levels boost telomere shortening, but studies on this link are scanty. We studied if, in barn swallows Hirundo rustica, changes in adult erythrocyte telomere length between 2 consecutive breeding seasons are related to corticosterone (CORT) (the main avian GC) stress response induced by a standard capture-restraint protocol. Within-individual telomere length did not significantly change between consecutive breeding seasons. Second-year individuals showed the highest increase in circulating CORT concentrations following restraint. Moreover, we found a decline in female stress response along the breeding season. In addition, telomere shortening covaried with the stress response: a delayed activation of the negative feedback loop terminating the stress response was associated with greater telomere attrition. Hence, among-individual variation in stress response may affect telomere dynamics.